Practical Considerations for the Use of Daratumumab, a Novel CD38 Monoclonal Antibody, in Myeloma - Moreau, P.; Van De Donk, N.W.C.J.; Miguel, J.S.; Lokhorst, H.; Nahi, H.; Ben-Yehuda, D.; Cavo, M.; Cook, G.; Delforge, M.; Einsele, H.; Zweegman, S.; Ludwig, H.; et al. (Drugs, 2016)
Monoclonal antibodies (mAbs) are a recent addition to multiple myeloma (MM) therapies and a number of mAbs directed at myeloma cell surface molecules are in development. Daratumumab is a CD38 mAb that has demonstrated substantial activity and good tolerability in four phase I, phase I/II and phase II studies as monotherapy, as well as in combination with current standard treatments in MM. The positive results obtained in the relapsed/refractory setting in patients with advanced-stage disease and in a small number of patients with newly diagnosed disease provide the rationale for the investigation of the agent in a number of ongoing phase III trials. mAbs are generally better tolerated than conventional chemotherapy; however, their use requires other special considerations. Such factors include those common to all mAbs, namely infusion-related reactions, but also factors that are observed with mAbs used in myeloma, such as interference with response assessment, or factors that are related to CD38 mAbs such as daratumumab, for instance blood typing interference. Our review provides an overview of the results from the daratumumab clinical trials conducted to date, as well as practical management considerations for the use of daratumumab based on our experience with the agent. © 2016 Springer International Publishing Switzerland.